(untitled) (Carte Romanze, 2023)
The paper provides the critical and commented edition of two poems, a contrasto between a disappointed lover and Eros. The main reason of interest is their belonging to the genre of the frottola, which continues to attract the attention of scholars for its unsolved problems of definition and edition. Moreover it is notable that in these two poems, proverbs and sententious motto, peculiar to the genre of the frottola, are replaced by echoes and memories of late fourteenth-century love poetry.